Editorial - Nuñez Vergara, Manuel (2016)
Guaranteeing the right to health, particularly in our country, is largely a challenge pending. The strategy chosen by Peru is the universal access to care and health care (1). However, it is notoriously absent or weak discussion on issues that support this strategy, such as care models, approaches in financing, construction (or not) of a single system of health and citizen participation, among others . We must make progress in these discussions, supporting with evidence and analysis, responses to issues that today are covered in the media, sometimes slightly, as the incorporation of EsSalud the scope of the health sector under the guidance of the Ministry of Health, the role of public - private partnerships, healthy eating and labeling of processed food, or the right of our patients to a fair, dignified and quality treatment, among others. But at the same time, we need to recognize that what should be on the basis of these issues is the need to recover an ethical vision of development, particularly in health claims 'first people' (2).